INTELEKTUAL ARENA PADA KKPK NEW BESTIES KARYA ORYZA SATIVA APRIYANI - Merpati, Rizky Dian (Universitas Negeri Surabaya, 2016)
Children's literature can be said that a literary work isinnya appropriate language and developmental age and the child's life, both written by authors who are already adults, adolescents or children themselves. The literary work is not only in the form of poetry and prose, but also the form of drama. This study examines the intellectual arena in the novel